IMPLEMENTASI BLOCKCHAIN DAN NON FUNGIBLE TOKEN (NFT) UNTUK MEMVALIDASI KEASLIAN DAN KEPEMILIKAN DOKUMEN RESMI - Azhar, Nur Fajri; Nasa’i Kairupan, Muhammad; Rusdianto Andarina Syakbani, Ahmad; Fadillah, Ansar (Jurusan Matematika dan Teknologi Informasi, 2023)
Data security and authenticity of ownership of private documents such as land certificates and identity cards or KTP are critical aspects of Indonesia's development process. Database system that has been implemented by the government to secure citizen's personal information is still susceptible to 6 major risk factors, namely, data breaches and theft, damaged data due to virus attacks, limited data storage space, data loss due to system damage, data can be accessed without certain access rights, as well as a lack of system certainty when security threats occur. The rampant cases of data counterfeiting and selling of KTP and land certificates have been a problem for the Indonesian government and have claimed lives for a long time. Based on the problem of public service management, this proposal suggests the development of a public service application for KTP and land certificates based on blockchain titled NFT Document Inspector to help mitigate risks contained in the Indonesian government`s database system as well as ensuring the authenticity of KTP and land certificates. The results of this research will provide insights for policy makers, practitioners and researchers regarding the adoption of blockchain mechanisms to secure citizen's private data in order to accelerate the digital transformation of public services for Indonesia to recover faster and rise stronger, which in this case is KTP and land certificate.